Դվինի 719 թ. Եկեղեցական ժողովի պատմականության խնդիրը - Անդրեաս Աբեղա Եզեկյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В арменоведении распространено мнение, что Св. Ованнес III Одзнеци (717–728 гг.) в 719 году в Двине созвал церковный собор, целью которого были осуществление церковных реформ и борьба с ересями.In the Armenology, it is common to state that Patriarch St. Hovhannes III of Odzoun (717–728) convened a Synod in Dvin in 719, aimed at the implementation of ritual-administrative improvements and struggle against heresies.
Keywords: History; Congregation